Community perspectives on access to maternal health services during the COVID-19 pandemic in rural Western Kenya: a qualitative study - Neema Kaseje; George Agango Odhiambo; Beldine Omondi; Andy Haines; Meghna Ranganathan (BMC Health Services Research)
Abstract Background Globally, maternal and child health outcomes were negatively affected during the COVID-19 pandemic. There is limited qualitative evidence focused on access to maternal health services during the COVID-19 pandemic in rural sub-Saharan African populations. This study aims to fill this gap by exploring key community perspectives on access to maternal health services during the COVID-19 pandemic in rural western Kenya. Methods We conducted five focus group discussions and sixty one in-depth interviews. Participants were mothers who delivered in 2020 during the acute phase of the COVID-19 pandemic and rural community health workers (CHWs) in Siaya and Kisii counties. The three-delay model framework helped to guide discussions around access to maternal health services during the COVID-19 pandemic in rural western Kenya. We transcribed the data and conducted a thematic content analysis. Results According to CHWs and expectant mothers, fear and misconceptions about COVID-19 were associated with delays in making the decision to seek maternal health care. Lockdowns, movement restrictions, and curfews made it challenging to physically reach health facilities. The shortage of drugs and supplies and an insufficient number of healthcare workers in health facilities were barriers to care seeking. The quality of maternal health services was perceived to have declined during the COVID-19 pandemic. Mothers reported the Linda Mama health insurance program helped them pay for maternal health services during the COVID-19 pandemic; however, out-of-pocket expenses were common. As reported by mothers, CHWs when engaged and active, helped alleviate access challenges by serving as a link to the health system. There were significant socio-economic difficulties experienced by community members because of closed businesses and schools. Conclusions Community perspectives revealed significant challenges with accessing maternal health services during the COVID-19 pandemic in rural western Kenya. The pandemic amplified each of three delays in accessing care leading to poorer access to maternal health services. The overriding perception among mothers was that CHWs helped mitigate challenges around access to health services. CHWs should be included in future pandemic preparedness and response efforts.